Frequency of Placental Abruption in Preterm Premature Rupture of Membranes (PPROM): Frequency of Placental Abruption in Preterm Premature Rupture of Membranes (PPROM) - Rani, Nadia; Iqbal, Nilofar; Waris, Tasmia; Gul, Sanila; Izhar, Muhammad (Pakistan Journal of Health Sciences, 2022)
Placental abruption is the premature separation of normally placed placenta. Its incidence is 1% worldwide in all pregnancies and 7% in Pakistan. Objective: To determine frequency of placental abruption in preterm premature rupture of membranes. Methods: This study was conducted in Department of obstetrics and gynecology DHQ Hospital Topi Swabi from 1st March 2021 to 31st October 2022. Total of 276 patients were recruited. Routine clinical examination was done for the confirmation of preterm PROM. All the patients were followed till delivery and placental abruption was diagnosed. All the mentioned information obtained were noted on a pre designed proforma. Results: Mean age was 33 ±2.17 years. Primi para and multi para were 40% and 60% respectively. Forty-two % patients were primi gravida, 58% patients were multi gravida. 33% mothers had gestational period of age range from 28-32 weeks while 67% patients had POG range 33-37 weeks. More over the frequency of placental abruption in preterm premature rupture of membranes was 5%. Conclusions: On the basis of results, it was concluded that active expectant management strategy and strict follow up minimizes the risk of occurrence of perinatal asphyxia, and neonatal morbidity and mortality